(3GdHMKs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ef ZQVfG ef cJGHfG gPG GdEMGWI dcfg Yde GdWdSeGJ hGdGTJeGd Ydi YedgG hUhQgG hCaYGdgG hGdChVGY hGdCOhGJ GdehUdI Edi ZGjI eG ajgG hVM GdWQb s
(3BNQgG (B:s
(3aCeG YWGA GdchGcH abO HGf cja jchf heG UhQJg hCeG GdcdGe ai CLRGFg hUZGFQI aj GdaUd GdJGdj dgPG GdaUd Ydi eG SfPcQg ajg hcPdc ai GdHGH GdPi jdj gPG GdHGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH Ydi WQagGs
(3hgj GdfSNI GdJGeI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs